Drug Discovery and Development of Novel Therapeutics for Inhibiting TMAO in Models of Atherosclerosis and Diabetes - Steinke, Ian; Ghanei, Nila; Govindarajulu, Manoj; Yoo, Sieun; Zhong, Juming; Amin, Rajesh H. (Frontiers in Physiology, 2020)
Diabetes mellitus exists as a comorbidity with congestive heart failure (CHF). However, the exact molecular signaling mechanism linking CHF as the major form of mortality from diabetes remains unknown. Type 2 diabetic patients display abnormally high levels of metabolic products associated with gut dysbiosis. One such metabolite, Trimethylamine N-Oxide (TMAO), has been observed to be directly related with increased incidence of cardiovascular diseases (CVD) in human patients. TMAO a gut-liver metabolite, comes from the metabolic degenerative product trimethylamine (TMA) that is produced from gut microbial metabolism. Elevated levels of TMAO in diabetics and obese patients are observed to have a direct correlation with increased risk for major adverse cardiovascular events. The pro-atherogenic effect of TMAO is attributed to enhancing inflammatory pathways with cholesterol and bile acid dysregulation, promoting foam cell formation. Recent studies have revealed several potential therapeutic strategies for reducing TMAO levels and is the central focus for the current review. However, few have focused on developing rational drug therapeutics and maybe due to the gaps in knowledge for understanding the mechanism by which microbial TMA producing enzymes and HFMO can work together in preventing elevation of TMAO levels. Therefore, it is critical to understand the advantages of developing a novel rational drug design strategy that manipulates HFMO production of TMAO and TMA production by microbial enzymes. This review will focus on the inspection of HFMO manipulation, as well as gut microbiota dysbiosis and its influence on metabolic disorders including cardiovascular disease and describe novel potential pharmacological therapeutic development.